2019
DOI: 10.1590/0034-7167-2017-0659
|View full text |Cite
|
Sign up to set email alerts
|

Workloads and burnout of nursing workers

Abstract: Objective: to identify workloads in nursing work and its association with nursing worker burnout. Method: a cross-sectional study, including 211 nursing workers from a university hospital, between July and August 2016. For the analysis, the descriptive statistics, Chi-Square Test, Fisher’s Exact Test and Mann Whitney U-Test were used. Results: the most evidenced loads were biological. A significant association was found between workloads and workers’ occupation, as well as a significant association between w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
20

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 14 publications
3
20
0
20
Order By: Relevance
“…Such characteristics attributed to labor are present in health work organization. However, nursing is the staff most affected, because, in addition to frequent accumulation of work relationships due to low wages, its activities include shortage of workers and wear and tear related to the complexity and heterogeneity of occupational activities in the hospital; these activities are configured as an overload for adding a greater load of material and immaterial work (1,(6)(7)(8)(9)(29)(30)38) .…”
Section: Strategies Of Nurse-midwives In Relation To Working Conditions In Maternity Hospitalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such characteristics attributed to labor are present in health work organization. However, nursing is the staff most affected, because, in addition to frequent accumulation of work relationships due to low wages, its activities include shortage of workers and wear and tear related to the complexity and heterogeneity of occupational activities in the hospital; these activities are configured as an overload for adding a greater load of material and immaterial work (1,(6)(7)(8)(9)(29)(30)38) .…”
Section: Strategies Of Nurse-midwives In Relation To Working Conditions In Maternity Hospitalsmentioning
confidence: 99%
“…It is assumed that work should be a source of pleasure and professional fulfillment; however, in adverse conditions and labor intensification, there is a greater chance that work will be a source of stress, frustration, depersonalization and discouragement, compromising the functional and moral capacity of workers, as well as the quality of health care (1)(2)4,(6)(7)(8)(9) . Therefore, it was found that participants are immersed in inadequate working conditions that conform to experiences of creative suffering, which is characterized by using the potential for reframing work through changes congruent with the desire of workers to resist destabilization at work.…”
Section: Strategies Of Nurse-midwives In Relation To Working Conditions In Maternity Hospitalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Em contrapartida, não há restrições pela organização do trabalho sobre o quantitativo de horas trabalhadas, o que também causa estranhamento, pois a concentração e atenção caem, à medida que o profissional permanece muitas horas no posto de trabalho. Além disso, o ambiente hospitalar é insalubre, assim, a permanência por elevado tempo nesse local se traduz em risco à saúde do profissional (Carvalho et al, 2019).…”
Section: Experiência Vivida Na Contratação E Atuação Com Pacientes Daunclassified
“…Cabe refletir que esses sentimentos se intensificam e se avolumam a partir do caso descrito, em que os trabalhadores precarizados/uberizados são colocados nas tarefas mais arriscadas e tensas, por dias consecutivos e muitas horas. No entanto, infere que uma das estratégias para mitigar o sofrimento decorrente da pandemia é fazer pausas no trabalho e alternar o trabalhador entre atividades de alta e baixa tensão (Carvalho et al, 2019).…”
Section: Experiência Vivida Na Contratação E Atuação Com Pacientes Daunclassified